2022
DOI: 10.24843/eja.2022.v32.i06.p16
|View full text |Cite
|
Sign up to set email alerts
|

Portrait of the polemic of Fraud In Conventional and Sharia Insurance Company

Abstract: This study examines the effect of fraud on insurance companies, both conventional and sharia insurance, from 2017 to 2021. This study aims to describe the existence of fraud committed through systems or humans, whether intentional or unintentional, even in Conventional and Sharia Insurance companies. The independent variables used are financial stability, financial targets, manager supervision ineffectiveness, auditor turnover, board turnover, and dualism positions. The insurance companies sampled in this stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 15 publications
0
1
1
Order By: Relevance
“…Furthermore, this research aligns with the GONE theory, suggesting that holding multiple positions may stem from a sense of dissatisfaction with singular achievements, thereby introducing a greed factor conducive to fraudulent behavior. However, these findings diverge from prior studies by Fajri et al (2023), Kristiana and Hatta (2022), and Siddiq and Suseno (2019), which found no significant effect of the dualism position on fraudulent financial statements.…”
Section: The Effect Of Dualism Position On the Potential For Fraudule...contrasting
confidence: 99%
“…Furthermore, this research aligns with the GONE theory, suggesting that holding multiple positions may stem from a sense of dissatisfaction with singular achievements, thereby introducing a greed factor conducive to fraudulent behavior. However, these findings diverge from prior studies by Fajri et al (2023), Kristiana and Hatta (2022), and Siddiq and Suseno (2019), which found no significant effect of the dualism position on fraudulent financial statements.…”
Section: The Effect Of Dualism Position On the Potential For Fraudule...contrasting
confidence: 99%
“…In its annual report, the ICW Non-Governmental Organization identified seven types of corruption commonly practiced by village governments: theft, budget misuse, power abuse, unlawful levies, fabricated reports, budget reduction, and seductions [12], [13]. The bigger the organization's managed funds and the lower the ICS applied, the higher the chance for deliberate or accident fraud, as well as fraud perpetrated by people or systems [14], [15]. The ICS is an accounting system designed to provide adequate confidence in the achievement of three groups of goals (effectiveness and efficiency of operations, reputable financial reporting, and compliance with applicable regulations) established by the board of commissioners, management, and other company personnel [16].…”
Section: Introductionmentioning
confidence: 99%